EQUATION OF STATE AND CRYSTAL STRUCTURE OF SB2S3 BETWEEN 0 AND 10 GPA - Lundegaard L.F.; Miletich R.; Balic-Zunic T.; Makovicky E. (My University, 2003)
High-precision unit-cell volume data of stibnite, collected in the pressure range of 0-10 GPa, was used for fitting a third-order Birch-Murnaghan equation of state. The zero-pressure volume, bulk modulus and its pressure derivative were found to be 487.73(6) A3, 26.91(14) GPa and 7.9(1), respectively. A series of X-ray intensity data was collected in the same pressure range using a CCD-equipped Bruker diffractometer. The high-pressure structures were all refined to R1(|F0|>4σ) values of approximately 0.03. Crystal-chemical parameters as polyhedron volume, centroid and eccentricity were calculated for the seven coordinated cation positions using the software IVTON. The cation eccentricity appears to be a very useful tool for quantification of the lone electron pair activity. U2S3, Dy2S3 and Nd2Te3 are all isostructural with stibnite, but the cations in these materials have no lone electron pair. Their eccentricity is much smaller than that of Sb, and close to zero. This confirms that the stibnite structure type alone does not force eccentricity upon the cations involved and it is the lone electron pairs of Sb that generate the eccentricity of cation positions in the structures of stibnite. At increasing pressure the eccentricity of Sb is decreasing. It is therefore reasonable to conclude that the lone electron pair activity is decreasing with increasing pressure.
Keywords: STIBNITE; HIGH PRESSURE; LONE ELECTRON PAIR; EQUATION OF STATE